Separation of Water-Oil Emulsion Using Polyethersulfone Membranes Treated With High-Frequency Low-Temperature Plasma - Dilshatovich Fazullin, Dinar; Vitalievich Mavrin, Gennady; Olegovich Dryakhlov, Vladislav; Gilmanovich Shaikhiev, Ildar; Rashatovich Nizameyev, Irek (International Journal of Psychosocial Rehabilitation, 2019)
A study of the water-oil emulsion separation by polyethersulfone membranes with a mass of cutoff particles 10 kDa was carried out. The membranes were treated with a low-temperature high-frequency capacitive reduced pressure plasma in an argon and nitrogen medium (70:30) at a voltage of U a = 1.5-5.5 kV and processing time τ = 1 5-7 minutes. Round flat filter elements with a diameter of 47 mm were used in the capacity of membranes. The emulsion with a concentration of 3% (by volume) was prepared on the basis of Devon oil from the Tumutukskoye oil field and distilled water and was stabilized by the Kosintol-242 surfactant. The experiments were carried out on a laboratory ultrafiltration separation unit. Based on the results of the studies, an increase in the separation productivity of the water-oil emulsions after plasma treatment of the membranes is shown; an increase in the studied process efficiency from 95.1 to 98.4% with the exposure by plasma at U = 3.5 kV and τ = 7 min is noted. Using electron microscopy, sedentary droplet, and IR spectroscopy methods, we have revealed an increase in the surface roughness of the membranes after plasma treatment with nitrogen argon, as a result of which the contact angle of distilled water decreased from 75.3˚ to 65.3˚, which indicates an increase in hydrophilicity and, respectively, water absorption, and in addition, the formation of oxygen-containing functional groups and the hydrogen bonds in the surface structure of the polymer polyethersulfone membrane.